Mechanism of Dihydromyricetin on Inflammatory Diseases - Sun, Yang; Liu, Shasha; Yang, Songwei; Chen, Chen; Yang, Yantao; Lin, Meiyu; Liu, Chao; Wang, Wenmao; Zhou, Xudong; Ai, Qidi; Wang, Wei; Chen, Naihong (Frontiers in Pharmacology, 2022)
Inflammation plays a crucial role in a variety of diseases, including diabetes, arthritis, asthma, Alzheimer’s disease (AD), acute cerebral stroke, cancer, hypertension, and myocardial ischemia. Therefore, we need to solve the problem urgently for the study of inflammation-related mechanisms. Dihydromyricetin (DHM) is a flavonoid mainly derived from Ampelopsisgrossedentat. DHM possesses many pharmacological effects, including anti-inflammatory (NLRP-3, NF-κB, cytokines and, neuroinflammation), antioxidant, improving mitochondrial dysfunction and, regulating autophagy. In this review, we reviewed the literature in recent 20 years and summarized the mechanism of DHM in inflammation. In addition, we also introduced the source, chemical structure, chemical properties, and toxicity of DHM. We aim to deepen our understanding of DHM on inflammation-related diseases, clarify the relevant mechanism of action, and find urgent problems to be solved. Providing new ideas for DHM drug research and development, as well as broaden the horizons of clinical treatment of inflammation-related diseases in this review. Moreover, the failure of clinical transformation of DHM poses a great challenge for DHM as an inflammation related disease.